Hybrid monsters in the Classical World : the nature and function of hybrid monsters in Greek mythology, literature and art - Posthumus, Liane (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Ancient Studies))--University of Stellenbosch, 2011.